A Qualitative Understanding of Local Traditional Knowledge and Medicinal Plant Use - Fassil, Hareya (World Bank, Washington, DC, 2012)
In Ethiopia, traditional herbal medicine is dominated by plant-focused work, which has been largely driven by an overriding interest in the specific therapeutic properties of individual plants. In search of information on the properties of various Ethiopian medicinal plants, researchers have generally focused their attention on two main sources: (i) the professional traditional health practitioners, and (ii) Ethiopia's ancient medico-religious manuscripts - herbal letters containing elaborate recipes of plant-derived treatments for a wide range of health conditions. Traditional knowledge about medicinal plants and its application are very much taken for granted by both men and women in the communities. Such traditional knowledge and practices constitute routine aspects of daily life and are deeply engrained in the socio-cultural and economic fabric of these rural societies. It is evident that research and development efforts must aim to identify and address the challenges and threats faced by traditional health knowledge systems. The ultimate goal is to strengthen and improve this vast knowledge base for the benefit of the great majority of the developing world who have survived on it for centuries and will continue to do so into the foreseeable future.